Management plan of geological hazard threats in the fault zone of adjacent open-pit mines - Guangwei LIU; Junxiong TU; Xianshuai MA; Yong YAO; Liang WANG; Meiling ZHAO (Meitan kexue jishu)
In the development of large-scale open-pit coal fields in China, there are often several Coal companies entering the same coal field, and each Coal company is a main body of development, mining coal resources in the state-allocated strip area, and building several open-pit mines at the same time or successively. Adjacent open-pit mines, during the excavation process, are susceptible to landslide hazards, particularly on the slopes where the adjacent end gangs, influenced significantly by the mining activities of both mines, reach the boundary. The Shengli West 2 open-pit coal mine and Wulantuga Zhemei open-pit mine are neighbouring surface mines in the same coal field, and the mining rights of the two mines do not overlap at the neighbouring end gangs, resulting in the formation of a trapezoidal platform between the west gang of the West 2 open-pit mine and the east gang of the Zhemei open-pit mine, and the impact of the overlying fault fragmentation zones and the operations of the two mines, which resulted in the appearance of signs of geologic hazards within the platforms, such as bottom drums, fissures, and collapse of faults. With the development of the stripping project of the two mines and the leaning operation of the adjacent end gangs, a steeper irregular platform will be generated between the adjacent end gangs and the boundary slopes, in order to avoid the occurrence of catastrophic landslides, and on the basis of the stability analysis of the steep platform, the treatment method of “digging out and backfilling as a whole” was put forward and the specific treatment plan was determined. The management plan specifies the scope of operation of the “overall excavation and backfilling” management method, and designs the shape of the clean-up work gang and the slope of the internal discharge site when the management is completed, which can completely eliminate the hidden geological hazards and release 9 318 300 m3 of internal discharge space in the West Second Open Pit Mine and 7 646 900 m3 of internal discharge space in the Zhemei open-pit mine Mine, so that the two mines can continue to achieve complete internal drainage. The results of this research provide the necessary theoretical basis and technical support for the treatment of geological hazard hidden bodies in the adjacent fault zones of the West 2 and Zhemei open-pit mines, and also provide relevant experience for the implementation of geological hazard management in similar adjacent open-pit mines in the same coal field.